Gabi ng… anek daw?! an exploration of the podcast persona of Gabi ng Bading with AC and Yani (2021) through its registers of performance - Malijan, Trinity Anne S.
This study investigates how a podcast constructs and performs an online persona through the lens of registers of performance, as theorized by Kim Barbour (2014). Focusing on Spotify-exclusive podcast Gabi ng Bading with AC and Yani (2021), hosted by content creators AC Soriano (@itsacslife) and Yani Villarosa (@yanihatesu), this study explores how the podcast develops a persona as a post-human identity. Using textual analysis, guided by Spinelli and Dan’s (2019) close analytical listening and Connell’s (2021) methodology, nine episodes selected through purposive sampling are examined to identify and analyze the podcast's professional, personal, and intimate registers. These registers were evaluated through three analytical foci: (1) language of the persona, (2) narrative, and (3) sonic language. Findings reveal that Gabi ng Bading (2021) negotiates these registers to strategically build a podcast persona, through a collection of digital artifacts, that is credible, relatable, and emotionally resonant. By centering the registers of performance as a framework, the study offers a nuanced understanding of persona construction in audio media and contributes to emerging discourses in podcast studies and persona studies, especially within the Philippine media context.